Empowering Reading Skills with Genially: Development of a Digital Snake and Ladder Game for Phase C Learners - Rahayu, Sari; Novita, Lina; Sukmanasa, Elly (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2024)
This study aims to empower reading skills of Phase C learners through the development of a digital snake and ladder game using the Genially application. The research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The analysis stage involved teachers, students, and instructional materials to identify the most suitable media for reading comprehension learning. Product feasibility was assessed through expert validation in media, content, and language. Effectiveness was further examined through reliability testing, normality, homogeneity, and hypothesis testing, complemented by pretest–posttest analysis using N-Gain. Limited trials were conducted with 16 students and expanded to 31 students in broader implementation. The results demonstrate that the Genially-assisted digital snake and ladder game, developed through the ADDIE model, effectively enhances reading comprehension. Expert evaluations confirmed its feasibility, while student feedback indicated higher engagement, motivation, and comprehension. Moreover, students’ reading comprehension scores improved by 39.7%, evidencing the significant contribution of interactive, game-based digital media to cognitive development. In conclusion, the Genially-assisted digital snake and ladder game is feasible and effective for empowering reading skills in Phase C learners, and it holds potential for adaptation in other learning materials.